Conformal Radiation Therapy for Pediatric Patients with Low-Grade Glioma: Results from the Children’s Oncology Group Phase II Study ACNS0221. - Cherlow, Joel M. (Int J Radiat Oncol Biol Phys, 2018)
PURPOSE: To determine the rate of marginal relapse, progression-free survival (PFS), and overall survival (OS) in patients with pediatric low-grade glioma (PLGG) treated with conformal radiation therapy (CRT) with a clinical target volume (CTV) margin of 5 mm in the Children’s Oncology Group trial ACNS0221. METHODS AND MATERIALS: Children (age 3–21 years) with unresectable progressive, recurrent, or residual PLGG were eligible for this study. Patients younger than 10 years were required to have received at least 1 chemotherapy course. Patients with neurofibromatosis type I were not eligible. All patients underwent MRI-based planning and received CRT 54 Gy in 30 fractions with a 5-mm CTV margin. RESULTS: Of 85 eligible patients (median age 13.6 years) treated between March 2006 and December 2010, 14 were younger than 10 years and 36 received prior chemotherapy. Sixty-six had pilocytic astrocytoma (PA); 15 had other histologic subtypes, and 4 had unbiopsied chiasmatic lesions. Events included 23 relapses - 19 central 4 distant, and no marginal - and 7 deaths. At a median follow-up of 5.15 years, 5-year PFS was 71%±6% and OS was 93%±4%. Male gender (P=.068) and large tumor size (P=.050) trended toward significance for association with decreased PFS. Age, histology, tumor location, time between diagnosis and study entry, and MIB-1 status were not associated with PFS. OS was negatively associated with male gender (P=.064), non-PA histology (P=.010), and large tumor size (P=.0089). CONCLUSIONS: For patients with PLGG, CRT with a CTV margin of 5 mm yields an acceptable PFS and does not lead to a high rate of marginal relapse.